Influence of Parental-Child Rearing Behavior in the Emotional Adjustment of Elementary School Pupils in Al-Nasiriyah City - Shareaf Ghazi, Sahar; Abed Neamah, Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Objective: identify the association between family socio economic status, pupil's age, pupil's birth order, parental-child rearing behaviors and child emotional adjustment; investigate the differences in pupil's emotional adjustment between group of parent's level of education, and pupil's gender. Methods: A descriptive study was used to guide this study. The study sample included 270 pupils who were selected randomly from 10 elementary schools in Al.Nasiriyah city, parents were identified through their children who compromised 140 boys from five schools and 130 girls from five schools data collection started from 19th of January,2020 to February 27th 2020. Data have been collected through using a questionnaire which consisted from three parts; the first part includes demographic data of study sample; the second part includes Parental Childrearing Behavior Scale (PCBS); and the third part includes the Child Emotional Adjustment Scale (CEAS). Data was collected through interview techniques. Descriptive and inferential statistical data analysis approaches are used. Results: There is no statistically significance differences between pupils' emotional adjustment and their family socioeconomic status and pupils' birth order, while there is statistically significant differences between pupils' emotional adjustment and pupils' age and parental-child rearing behavior. There is statistically significance differences between pupils' emotional adjustment and group of father level of education, there is statistically significance differences between pupils' emotional adjustment and group of mother level of education and there is no statistically significance differences between pupils' emotional adjustment and group of child gender. Conclusion: The study concludes there is there is no statistical significant differences between pupils' emotional adjustment their family socioeconomic status and pupils' birth order , while there is statistically significant differences between pupils' emotional adjustment and pupils' age and parental-child rearing behavior, there is significant statistical relationship between pupils emotional adjustment and groups of father and mother level of education. Recommendation: Design educational program that focus on parents and teachers how deal with children and increase their emotional adjustment skills. It is necessary to conduct similar studies for larger sample size in different areas across Iraq. The sample size can be increased and a comparative study can be made between public and private schools.